A systematic assessment of how rootstock growth characteristics impact grafted tomato plant biomass, resource partitioning, yield, and fruit mineral composition - Gong, Tian; Brecht, Jeffrey K.; Koch, Karen E.; Hutton, Samuel F.; Zhao, Xin (Frontiers in Plant Science, 2022)
The appropriate selection of rootstock-scion combinations to improve yield and fully realize grafting benefits requires an in-depth understanding of rootstock-scion synergy. Toward this end, we grafted two determinate-type scions [grape tomato (‘BHN 1022’) and beefsteak tomato (‘Skyway’)] onto four rootstocks with different characteristics to examine plant growth, yield performance, biomass production, and fruit mineral nutrient composition. Study was conducted during two growing seasons (Spring and Fall plantings in Florida) under organic production in high tunnels with the non-grafted scions as controls. Rootstocks had previously been designated as either “generative” (‘Estamino’) or “vegetative” (‘DR0141TX’) by some commercial suppliers or had not been characterized [‘RST-04-106-T’ and ‘SHIELD RZ F1 (61-802)’]. Also, ‘Estamino’, ‘DR0141TX’, and ‘RST-04-106-T’ had been described as more vigorous than ‘SHIELD RZ F1 (61-802)’. In both planting seasons (with low levels of soilborne disease pressure), the “vegetative” and “generative” rootstocks increased marketable and total fruit yields for both scions except for beefsteak tomato grafted with the “vegetative” rootstock in Fall planting. Positive effects of ‘RST-04-106-T’ on fruit yield varied with scions and planting seasons and was most manifested when grafted with the beefsteak tomato scion in Fall planting. ‘SHIELD RZ F1 (61-802)’ led to similar yields as the non-grafted controls except for grafting with the grape tomato scion in Fall planting. For vegetative and fruit biomass: Both “vegetative” and “generative” rootstocks had positive impacts except for beefsteak tomato in Fall planting. For fruit mineral composition: The “vegetative” and “generative” rootstocks, both highly vigorous, consistently elevated fruit P, K, Ca, Zn, and Fe contents on a dry weight basis, whereas the other rootstocks did not. Overall, although the more vigorous rootstocks enhanced tomato plant productivity and fruit minerals, evidence presented here does not support the suggestion that so-called “vegetative” and “generative” rootstocks have different impacts on tomato scion yield, biomass production, or fruit mineral contents. More studies with different production systems and environmental conditions as well as contrasting scion genotypes are needed to further categorize the impacts of rootstocks with different vigor and other characteristics on plant biomass production and its implications for fruit yield development.